Mechanistic and Kinetic approach to the Hydrolysis of Mono-p-nitro-Thiophenyl Phosphate in Acidic Media - Shinde, C.P.; Patil, R. (Asian Journal of Chemistry, 2010)
Investigation of p-nitro-thiophenyl phosphate was carried out, by using "Allen's" modified method of colorimetry, in aqueous medium from 0.1 to 7.0 mol dm3 HCl at 65ºC. pH log rate profile has a rate maximum at 4.0 mol dm3 HCl. Here mainly contribution of conjugate acid species of mono-thioate is involved in hydrolysis. Ionic-strength, temperature, solvent and concentration's kinetic studies provided to identify the reactive species and molecularity. Molecularity and bond-fission is also discussed in terms of Zücker-Hammett hypthesis, Hammett acidity founctions, Bunett and Bunett-Olsen parameters, isokinetic relationships and effect of temperature and solvent etc.